Slow development as an evolutionary cost of long life. (9th March 2017) - Lind, Martin I.; Chen, Hwei‐yen; Meurling, Sara; Guevara Gil, Ana Cristina; Carlsson, Hanne; Zwoinska, Martyna K.; Andersson, Johan; Larva, Tuuli; Maklakov, Alexei A.
Summary: Life‐history theory predicts a trade‐off between early‐life fitness and life span. While the focus traditionally has been on the fecundity‐life span trade‐off, there are strong reasons to expect trade‐offs with growth rate and/or development time. We investigated the roles of growth rate and development time in the evolution of life span in two independent selection experiments in the outcrossing nematode Caenorhabditis remanei . First, we found that selection under heat‐shock leads to the evolution of increased life span without fecundity costs, but at the cost of slower development. Thereafter, the putative evolutionary links between development time, growth rate, fecundity, heat‐shock resistance and life span were independently assessed in the second experiment by directly selecting for fast or slow development. This experiment confirmed our initial findings, since selection for slow development resulted in the evolution of long life span and increased heat‐shock resistance. Because there were no consistent trade‐offs with growth rate or fecundity, our results highlight the key role of development rate – differentiation of the somatic cells per unit of time – in the evolution of life span. Since development time is under strong selection in nature, reduced somatic maintenance resulting in shorter life span may be a widespread cost of rapid development. A lay summary is available for this article. Abstract : Lay Summary